Design and experimental study on vibration reduction of damping rings for four-branch star herringbone gear transmission - Linlin Liu; Sanmin Wang; Haoran Zou; Peng Chen (Results in Engineering)
The multi-branch herringbone gear transmission system is widely used in ships, aviation, and automobiles. However, under heavy loads and high speeds, it generates severe vibrations and noise, compromising reliability and service life. Installing damping rings on bull gears offers an effective vibration reduction solution. This study focuses on a four-branch star herringbone gear system, establishing a friction energy dissipation model for damping rings under axial and radial vibrations. The model quantifies the relationship between key parameters (friction coefficient, thickness, preload force) and equivalent damping. A multi-degree-of-freedom dynamic model integrates equivalent linear damping to analyze coupling effects between damping rings and gear meshing dynamics. Experimental results demonstrate that increasing the friction coefficient and preload force enhances energy dissipation capacity. A damping ring with a 2 mm thickness achieves a maximum vibration reduction rate of 10 % at 5000 rpm. Notably, axial equivalent damping significantly suppresses vibration acceleration in the z-direction, while radial damping amplifies vibrations in the x-direction, emphasizing the need for balanced parameter design. The study provides optimization criteria for engineering applications, advancing passive damping technology toward high efficiency and low noise in gear systems.